(3QSGdI ajef edc TjFG edc GdEbQGQ Hgs - (3GdJSJQj GdcGXej, CSO Gddg Hf ESeGYjd GdJSJQj GdcGXej, J (B1234(3g` (B1819(3es (... (3GdMSjfjIs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYd GdQLGd bhGejf Ydi GdfSGA (B... (3hHYO ajbhd GdeJeSc HLHd eYGOf GdJfRjd (B... (3gPG jG GNjs
(3BNQgG (B:s
(3BNQgG(B: (3hcGf Mce GdeCQI aj GdEQK Mce cd eWdbI KHJ WdGbgG HGdHjfI EP dG aQb Hjf LgGJ KHhJg ajeG PcQ hEf GaJQbJ ef HYV GdhLhg GdCNQ hEP bO dGM HeG MQQ hLg GdMb hGfaQO adjcf gPG BNQ eHdZ GdfaS hfJjLI GdacQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B1: 347s
(3GdPQjYI, L (B17: 10(3, (B31(3; (B19: 38s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis